Pregnancy after bariatric surgery: Consensus recommendations for periconception, antenatal and postnatal care. (16th August 2019) - Shawe, Jill; Ceulemans, Dries; Akhter, Zainab; Neff, Karl; Hart, Kathryn; Heslehurst, Nicola; Štotl, Iztok; Agrawal, Sanjay; Steegers‐Theunissen, Regine; Taheri, Shahrad; Greenslade, Beth; Rankin, Judith; et al.
Summary: The objective of the study is to provide evidence‐based guidance on nutritional management and optimal care for pregnancy after bariatric surgery. A consensus meeting of international and multidisciplinary experts was held to identify relevant research questions in relation to pregnancy after bariatric surgery. A systematic search of available literature was performed, and the ADAPTE protocol for guideline development followed. All available evidence was graded and further discussed during group meetings to formulate recommendations. Where evidence of sufficient quality was lacking, the group made consensus recommendations based on expert clinical experience. The main outcome measures are timing of pregnancy, contraceptive choice, nutritional advice and supplementation, clinical follow‐up of pregnancy, and breastfeeding. We provide recommendations for periconception, antenatal, and postnatal care for women following surgery. These recommendations are summarized in a table and print‐friendly format. Women of reproductive age with a history of bariatric surgery should receive specialized care regarding their reproductive health. Many recommendations are not supported by high‐quality evidence and warrant further research. These areas are highlighted in the paper.